2017
DOI: 10.1186/s12906-017-1811-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest and apoptosis induction by methanolic leaves extracts of four Annonaceae plants

Abstract: Background Uvaria longipes (Craib) L.L.Zhou, Y.C.F.Su & R.M.K.Saunders, Artabotrys burmanicus A.DC, Marsypopetalum modestum (Pierre) B.Xue & R.M.K.Saunders and Dasymaschalon sp. have been used for traditional medicine to treat cancer-like symptoms in some ethnic groups of Thailand and Laos.MethodsWe evaluated the anti-cancer activity of these Annonaceae plants against several human cancer cell lines. The apoptosis induction was detected by Annexin/propidium iodide (PI) staining. Phytochemical screening was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The consumption of fungal extract by larvae also significantly reduced the percentage of living cells and increased the percentage of apoptotic and necrotic cells showing the cytotoxic effect of fungal extract. Different researchers have evaluated the cytotoxic and apoptotic effects of different plants as well as fungal extracts on various cell lines 52 55 . Fernando et al .…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of fungal extract by larvae also significantly reduced the percentage of living cells and increased the percentage of apoptotic and necrotic cells showing the cytotoxic effect of fungal extract. Different researchers have evaluated the cytotoxic and apoptotic effects of different plants as well as fungal extracts on various cell lines 52 55 . Fernando et al .…”
Section: Discussionmentioning
confidence: 99%
“…TA provokes apoptosis, which has been confirmed by phosphatidylserine externalization, cleaved caspase-3 level and loss of membrane potential in mitochondria. Other studies also found that TA arrested the cell cycle and increased the percentage of cells in the SubG1 phase in some cancer cell lines [ 201 , 205 , 206 ]. In addition, TA could protect against skin tumor promotion induced by UV radiation in an in vivo study [ 207 ].…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 82%
“…Rutin has a high therapeutic value because it relieved the symptoms of several diseases like lymphatic and venous insufficiency, hemorrhagic diseases, and hypertension and due to its excellent hepatoprotective effect [ 32 ]. Though the cytotoxicity of rutin on cultured human cells is still debated, its marked cytotoxicity on different cancer cell lines has been widely reported [ 33 35 ]. It was found to induce apoptosis in prostate cancer cells, LNCaP at low concentration and in liver cancer cells, and HepG2 at very high concentration by acting as prooxidant instead of an antioxidant.…”
Section: Resultsmentioning
confidence: 99%